SAT0038 CHANGES IN ILLNESS PERCEPTIONS IN PEOPLE WITH RHEUMATOID ARTHRITIS OVER THE FIRST YEAR OF TREATMENT WITH METHOTREXATE. (13th June 2020) - Gwinnutt, J.; Norton, S.; Hyrich, K.; Lunt, M.; Barton, A.; Cordingley, L.; Verstappen, S.
Abstract : Background: Illness perceptions at treatment onset are known to be important predictors of treatment response in rheumatoid arthritis (RA). Yet it is unknown how these perceptions change over time after the initiation of treatment, or which factors are associated with changing perceptions. Objectives: To identify groups of patients with early RA who have similar changes in illness perceptions over the first year following treatment, and assess predictors of these changes. Methods: Patients starting methotrexate (MTX) for the first time were recruited to the Rheumatoid Arthritis Medication Study (RAMS), a one-year prospective cohort. The DAS28 was calculated and patients completed a questionnaire at baseline and 12 months, reporting demographics and completing the HAQ, the Hospital Anxiety and Depression Scale (HADS), pain and fatigue visual analogue scales (VAS) and the Brief Illness Perception Questionnaire (B-IPQ). The B-IPQ consists of eight Likert scales: five represent cognitive illness perceptions (B-IPQ1-5), two represent emotional representations (B-IPQ6 & 8) and one represents illness comprehensibility (B-IPQ7). Change in illness perceptions and EULAR response were calculated over 12 months in those with data at both timepoints. Latent profile analysis was used to identify profiles of patients with similar changes in illness perceptions. Candidate predictors of profile membership were assessed using logistic regression. The association between profile and EULAR response was assessed using ordered logistic regression. Results: In total 1188 patients were included (mean [SD] age: 59.8 [12.7], 781 [65.7%] women). On average, illness perceptions for the whole cohort improved over 12 months, other than patients' perception of longevity of arthritis (B-IPQ2) and of treatment helpfulness (B-IPQ4). Three profiles were identified: Small Improvers (N=900), Small Deteriorators (N=78) and Large Improvers (N=210) (Figure). Small Improvers improved on all B-IPQ items other than their perception of longevity of arthritis (B-IPQ2) and of treatment helpfulness (B-IPQ4). All B-IPQ items improved in the Large Improvers group to a greater extent than the Small Improvers, other than arthritis longevity (B-IPQ2). The perceptions of Small Deteriorators all worsened, other than arthritis comprehensibility (B-IPQ7). Higher baseline pain was associated with greater odds of being in both the Small Deteriorators and Large Improvers compared to Small Improvers (Small Deteriorators: OR 1.56 per standard deviation (SD) increase in pain [95% CI 1.11, 2.18]; Large Improvers: OR 1.46 per SD increase in pain [95% CI 1.15, 1.85]). Odds of better EULAR response were greater in the Large Improvers (OR 4.37 [95% CI 3.01, 6.33]) and worse in the Small Deteriorators (OR 0.50 [95% CI 0.29, 0.87]) compared to Small Improvers. Conclusion: In general, illness perceptions improved over the first year of MTX treatment and improvements were associated with better treatment response. Worsening illness perceptions may be driven by poor treatment response. These poor illness perceptions at follow-up may compound poor treatment response in the future. Greater understanding of patients' initial and subsequent illness perceptions is crucial, given the association with treatment response. Figure: Disclosure of Interests: James Gwinnutt Grant/research support from: BMS, Sam Norton: None declared, Kimme Hyrich Grant/research support from: Pfizer, UCB, BMS, Speakers bureau: Abbvie, Mark Lunt: None declared, Anne Barton Consultant of: AbbVie, Lis Cordingley Grant/research support from: Unrestricted award from Pfizer unrelated to current abstract, Speakers bureau: Janssen, AbbVie, Celgene, Sanofi, Eli Lilly, Novartis all unrelated to current abstract, Suzanne Verstappen Grant/research support from: BMS, Consultant of: Celltrion, Speakers bureau: Pfizer